2017
DOI: 10.1002/chem.201604780
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalysed Cross‐Coupling Reactions Controlled by Noncovalent Zn⋅⋅⋅N Interactions

Abstract: Non-covalent interactions between halopyridine substrates and catalytically inert building blocks, namely zinc(II)-porphyrins and zinc(II)-salphens, influence the catalytic outcome of Suzuki-Miyaura and Mizoroki-Heck palladium-catalysed cross-coupling reactions. The weak Zn⋅⋅⋅N interactions between halopyridine substrates and zinc(II)-containing porphyrins and salphens, respectively, were studied by a combination of H NMR spectroscopy, UV/Vis studies, Job-Plot analysis and, in some cases, X-ray diffraction stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 135 publications
1
12
0
Order By: Relevance
“…Having established that structurally equivalent supramolecular ligands L2 – L4 were able to bind in a different manner to bromopyridines P2 – P4 by exclusive tuning of the binding capabilities of the embedded metal center (Zn, Cu, Ru), we investigated these ligands in representative Pd‐catalyzed Suzuki–Miyaura reactions. Toluene was used as solvent because its relatively low polarity favors the interaction between pyridine derivatives and metalloporphyrins . We also hypothesized that the weakly coordinating properties of toluene would enhance the binding of nitrile groups to catalytically active palladium ions.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Having established that structurally equivalent supramolecular ligands L2 – L4 were able to bind in a different manner to bromopyridines P2 – P4 by exclusive tuning of the binding capabilities of the embedded metal center (Zn, Cu, Ru), we investigated these ligands in representative Pd‐catalyzed Suzuki–Miyaura reactions. Toluene was used as solvent because its relatively low polarity favors the interaction between pyridine derivatives and metalloporphyrins . We also hypothesized that the weakly coordinating properties of toluene would enhance the binding of nitrile groups to catalytically active palladium ions.…”
Section: Resultssupporting
confidence: 89%
“…Different binding behaviors associated with the bulkiness of substrates P2 – P4 and the nature of the metal center embedded in L2 – L4 were evidenced. For instance, P2 did not bind to any metalloporphyrin ligand due to pronounced steric effects imposed by the ortho substitution pattern . On the other hand, P3 and P4 did reversibly bind to both Zn‐containing L2 and Ru‐containing L3 in 1:1 stoichiometry with comparable thermodynamic strengths ( K 1.1 ≈10 3 –10 4 m −1 , Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… [15a] The relevance of the substrate binding to the zinc(II)‐porphyrin pocket was further evidenced by the lack of reactivity observed for pyridines having no lone pair available for binding (pyridinium derivatives, Scheme 3 C) as well as for pyridines unable to bind to the zinc atom owing to steric shields (2‐methylpyridine, Scheme 3 C). [28, 29] A last experiment was performed adding to the standard reaction conditions zinc(II)‐salphen ( ZS ) as a substrate competitive inhibitor (Scheme 3 D) since it is known that zinc(II)‐salphen derivatives bind to pyridine derivatives typically two orders of magnitude higher than zinc(II)‐porphyrins [28a, 30] . In this scenario, an almost complete inhibition of catalysis took place with one equivalent of ZS .…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the reactivity of chloro-and bromo-pyridines in palladium-catalyzed Suzuki and Heck was strongly affected by the presence of zinc-containing scaffolds in the reaction mixture. 162 Increased reaction rates and reactivity were observed for those substrates able to interact with the zinc-containing scaffolds because they were involved in secondary Zn•••N coordination whilst the palladium catalyst was operating. On the other hand, the substrates that did not interact with zinc-scaffolds led to catalyst deactivation by overcoordination of the substrate (or product) to the palladium centre.…”
Section: Znmentioning
confidence: 99%